Dominant mode selection and modal coupling analysis for wind-induced response of long-span roofs. Issue 4 (April 2017) - Li, Yuxue; Shi, Kai; Yang, Qingshan; Tian, Yuji
Mode selection and modal coupling analysis are important to estimate wind-induced structural response of long-span roof structures. This article presents a framework for predicting wind-induced structural response of long-span roof structures based on modal analysis. This framework first identifies the dominant modes according to the correlation between the mode shape and the wind load spatial distribution on the structure as well as a proposed "modal participation coefficient." Second, the concept of modal strain energy is introduced and a modal coupling coefficient is defined, based on which the dominant coupling modes are determined. A modified square root of the sum of the squares methodology is then developed to account for the modal coupling effects of the background and the resonant response components. The total responses can be obtained by combining the contributions of the dominant coupling modes and the square root of the sum of the squares results from the dominant modes. This avoids the use of the computation expensive complete quadratic combination method. Finally, an illustrative example of wind-induced response analysis of the China National Stadium roof structure is provided to demonstrate the effectiveness of the proposed framework.